Spatio-temporal Diptera visitation to Silene acaulis flowers studied with time-lapse cameras in Svalbard and Greenland - Klausen, Line (UiT Norges arktiske universitet, 2022)
Flower visitation by flying arthropods has mainly been studied by direct human observation, which usually neglects seasonal development of flower abundance even though this is known to be important for visitor dynamics and match between trophic levels. In the present study, the arthropod visitor community focusing on Diptera was investigated on the cushion plant Silene acaulis (L.) Jacq. in relation to the available flower area. This was done using time-lapse cameras at one sub-Arctic, one low Arctic, and two high Arctic sites at Svalbard and Greenland. The S. acaulis flower visitor match at the Svalbard site was in addition characterized by using independent invertebrate traps located next to the camera site. Image annotation of cushion’s visitors ensured a high temporal resolution of data throughout the flowering season and showed a highly increased visitation frequency when more flowers were open. Individuals from several trophic levels visited S. acaulis, supporting the claim of S. acaulis as nursing plant and community hotspot. True flies (Diptera) were by far the most abundant visitors of the visitors identified. The Diptera visitor abundance per unit flower area showed large variations and varied over seasonal development, years, and between sites. Image-annotated visitors were observed both on open flowers and the remaining image. In average 40 % of Diptera visitors were observed on flowers. This percentage followed the increase in image area with open flowers and peaked the same time as flowering peak, thought the number was also site and year specific. For the largest camera site in Svalbard, this percentage of visitors on flowers strongly decreased during the three-year study period. The decrease may have been enhanced by delays in flowering onset that led to increased competition with other flower species, making S. acaulis flowers less attractive to visitors.